O Organic substrates in the development of camu-camuzeiro (Myrciaria dubia (H. B. K.) McVaugh) in the amazon region - Bronze, Antonia Benedita da Silva; Brito, Sinara de Nazaré Santana; Monteiro, Harleson Sidney Almeida; Sena, Ewerton Delgado; da Silva, Nayara Ferreira Barros; Pinheiro , Valdeci Junior Fonseca; Abreu , Layse Barreto de Almeida; Dias, Rhuan Carlos Nascimento (Comunicata Scientiae, 2023)
Amazon is the largest tropical forest on the planet, it has a variety of plant species with emphasis on many fruit trees, such as the camu-camuzeiro (Myrciaria dubia (H. B. K.) McVaugh), which occurs naturally on the banks of rivers, lakes, lowlands and flooded forest of the Amazon. The objective of this study is to evaluate the development of camu-camuzeiro seedlings in different organic substrates. The experiment was conducted in the seedling production nursery of the Federal Rural University of Amazon. The experimental design was entirely randomized, with ten treatments and five repetitions, each portion was represented by ten plants, totaling 500 seedlings. The substrates evaluated were: T1 - Humus; T2 - Humus + Bird manure; T3 - Humus + Bovine manure; T4 - Humus + Açaí kernel; T5 - Humus + Chestnut shell; T6 - Humus + Chestnut shell + Poultry manure; T7 - Humus + Bovine manure + Chestnut shell; T8 - Humus + Açaí kernel + Poultry manure; T9 - Humus + Açaí kernel + Bovine manure; T10 - Commercial. The different substrates used influenced the development of camucamuzeiro seedlings evaluated at 180 days. The treatments with a substrate based on Humus (T1), Humus + Açaí kernel (T4), Humus + Chestnut shell (T5), Humus + Chestnut shell + Poultry manure (T6), Humus + Bovine manure + Chestnut shell (T7), Humus + Açaí Kernel + Bovine manure (T9) and the commercial substrate (T10) are the best for a satisfactory development of this crop in the production field.